Institutional context and place-based policy: the case of Coventry & Warwickshire - Glückler, Johannes (Growth and change, 2020)
A key problem of downscaling or transferring policies across regions is embedding these policies into a place for them to unleash the full potential of regional economies. This paper elaborates on the analytical framework of “institutional context” to bridge the gap between rich theorizations and poor empirical capture of institutions in studies of regional development. The institutional context is constituted by three pillars—regulations, organizations, and institutions—as well as by the interrelations between these pillars. Applied to the British region of Coventry and Warwickshire, a qualitative analysis of expert interviews finds institutional patterns of short-termism, moderate levels of social capital and an embryonic relational infrastructure to constrain the place-based strategy for industrial diversification. This regional case illustrates the more general challenge for regional policy in the UK of devising place-based strategies under conditions of continuous rescaling of regional governance and the implementation of a new National Industrial Strategy. In conclusion, the analysis suggests a shift from “nodal” to “linking” policies that support cross-network connections and help grow a regional field for collective action to cross-fertilize knowledge and foster innovation and entrepreneurship in emerging industries.